Influência do horário de aplicação no residual de Dipel® no controle de Chrysodeixis includens (lepidoptera noctuidae) - Batista, Djeferson José de Oliveira (2024)
The species Chrysodeixis includens, commonly known as the soybean looper, is one of the main pests in soybean cultivation in Brazil. Its control is based on chemical insecticides and Bt plants, however, the history of resistant populations in other countries may complicate the management of this pest. Bacillus thuringiensis (Bt) based bioinsecticides are alternatives that help in control and can delay the appearance of resistant populations of the looper, being an economically sustainable option. However, these products have low field persistence due to sensitivity to climatic factors such as UV rays, making it difficult to maintain product effectiveness in the field. This study aimed to evaluate different application times of the biological insecticide Dipel® and its field persistence in controlling the soybean looper. The experiments were conducted at UFSM in Santa Maria/RS during the years 2021, 2022, and 2023. The treatments consisted of three application times (8:00 AM, 12:00 PM, and 6:00 PM), with leaf collection immediately after spraying, and 24, 48, and 72 hours after. The samples were cut and placed in 100mL plastic cups to conduct a bioassay with the infestation of two 2nd instar larvae in each container, totaling 84 larvae in the years 2021 and 2022 and 96 larvae in 2023 per treatment. No application was made in the control group, resulting in a factorial scheme ([3x4]+1). Mortality evaluation was performed five days after setting up the bioassay. The different application times did not show significant differences in the product's effectiveness on the mortality of C. includens, but pest control was reduced the longer the leaves were exposed to field climatic conditions, achieving better control immediately after application up to the first 24 hours.